Answer:
x = 3, y = -1
Explanation:
The system of equations to solve is:
![2x-3y=9\\3x+5y=4](https://img.qammunity.org/2021/formulas/mathematics/high-school/3048prp8oozg5wekwszch4c8yym9hvz7xs.png)
We proceed as follows:
1) First of all, we multiply equation (1) by 3, and we get:
(1)
2) Then, we multiply equation (2) by 2, and we get:
(2)
3) Now we notice that the coefficient of the variable x is the same in the 2 equations; so, we subtract eq(1) from eq(2), and we get:
![(6x-6x)+(10y-(-9y))=8-27\\19y=-19](https://img.qammunity.org/2021/formulas/mathematics/high-school/j473ulzhugaux7aukoocwhrnlsusex9yml.png)
4) We solve this equation for y, and we get:
![y=(-19)/(19)=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/jwjzzoyjm80a4zyj94nr6ihteivryu8yt5.png)
5) We substitute this value of y back into the original equation (1), and we solve for x:
![2x-3y=9\\2x-3(-1)=9\\2x+3=9\\2x=9-3=6\\x=(6)/(2)=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/4bzueuyw8ktcvvno2x2ho1opxpeoc12bqi.png)